Private adaptation in semi-arid lands: a tailored approach to 'leave no one behind'. (2020) - Gannon, Kate Elizabeth; Crick, Florence; Atela, Joanes; Babagaliyeva, Zhanna; Batool, Samavia; Bedelian, Claire; Carabine, Elizabeth; Conway, Declan; Diop, Mamadou; Fankhauser, Sam; Jobbins, Guy; Ludi, Eva; et al.
Non-technical abstract: Globally, semi-arid lands (SALs) are home to approximately one billion people, including some of the poorest and least food secure. These regions will be among the hardest hit by the impacts of climate change. This article urges governments and their development partners to put SAL inhabitants and their activities at the heart of efforts to support adaptation and climate resilient development, identifying opportunities to capitalize on the knowledge, institutions, resources and practices of SAL populations in adaptation action. Technical abstract: Semi-arid lands (SALs) in developing countries are climate change 'hotspots' where climate hazards will affect poor populations disproportionately. This represents a major threat to the 2030 Sustainable Development Agenda pledge to 'leave no one behind'. In this paper we argue that national governments have underestimated opportunities to support climate resilient development in SALs and highlight ways in which the resilience of SAL populations has been undermined by current top-down approaches to adaptation and development. We argue a radical shift in national policy landscapes is required that refocuses on leveraging the existing adaptive capacities of private actors – women, farmers, cooperatives and firms – to cope with and respond to prevailing environmental shocks and weather extremes. This, we argue, requires providing enabling business environments that are tailored to the diverse and specific needs of the private sector in SALs and which support the full range of private sector actors in SALs to meet the challenges and opportunities of climate change. In doing this, we identify opportunities to overcome structural weaknesses that currently contribute to a lack of private investment, undermine important resilience strategies and limit opportunities to unlock broader resilience in SALs through the private sector.